Psychological factors of microsocial characteristic of teenagers' Internet-addiction behavior - Prokopovich, Eugen; Pilguk, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article presents the results of empirical research microsocial (psychological problems caused by the immediate social environment) factors of Internet addiction of adolescents.
Keywords: Internet addiction; adolescence; addictive behavior; parental authority